Upaya Meningkatkan Kreativitas Seni Anak melalui Kegiatan Teknik Kolase - Yulida Yulida; Veryawan Veryawan (Atfaluna: Journal of Islamic Early Childhood Education, 2018)
This research is done because of the low level of creativity of children's art through collage techniques in group B in TK Kartika I-49 Padangsidimpuan. The formulation of the problems researched is how to improve the creativity of children's art through collage technique activity. The research conducted was a research of professional capability, consisting of two observations, consisting of four stages, namely planning, implementation, observation and reflection. The subject of the researcher is the son of group B in TK Kartika I-49 Padangsidimpuan by using instruments i.e. observation sheets and data analysis used that is a qualitative data analysis technique that can be seen from the children art creativity through activities a collage technique and quantitative data that has been calculated with the formula. The results of the research gained in the child's subtle ability increase after action. After conducting research cycle I gained 44% and in cycle II increased to 88%. It was concluded that the creativity of children's art through collage techniques of group B in TK Kartika I-49 Padangsidimpuan had increased.